The role of light in regulating plant growth, development and sugar metabolism: a review - Wu, Wenyuan; Chen, Long; Liang, Rentao; Huang, Shiping; Li, Xiang; Huang, Bilei; Luo, Huimin; Zhang, Miao; Wang, Xiaoxun; Zhu, Hua (Frontiers in Plant Science, 2025)
Light provides the necessary energy for plant photosynthesis, which allows plants to produce organic matter and energy conversion, during plant growth and development. Light provides material energy to plants as the basis for cell division and differentiation, chlorophyll synthesis, tissue growth and stomatal movement, and light intensity, photoperiod, and light quality play important roles in these processes. There are several regulatory mechanisms involved in sugar metabolism in plants, and light, as one of the regulatory factors, affects cell wall composition, starch granules, sucrose synthesis, and vascular bundle formation. Similarly, sugar species and genes are affected in the context of light-regulated sugar metabolism. We searched the available databases and found that there are fewer relevant reviews. Therefore, this paper provides a summary of the effects of light on plant growth and development and sugar metabolism, further elaborates on the mechanisms of light effects on plants, and provides some new insights for a better understanding of how plant growth is regulated under different light conditions.